[The role of zakat in achieving community security from the point of view of management and supervisory staff in zakat institutions in Palestine] - Siti Fatimah, Salleh; Mostafa Hassan, Mohamed El Khayat; Dima Fayaq, Abulatefa (Penerbit Universiti Sultan Zainal Abidin, 2019)
This study seeks to understand the role of the zakat obligation in terms of achieving the social security from the point of view of the management and supervision staff in the zakat institutionsPalestine. The research adopts the descriptive approach to apply the study on a sample consists of 105 employees. The questionnaire consisting of 28 questions was applied in May, 2019. The questionnaire discusses four points concerning with; facing the poverty, reducing the unemployment, distributing the wealth and achieving the equality. The study exposes that the total average of the results coming from investigating the role of the Zakat in achieving the social security in terms of facing the poverty, reducing the unemployment, distributing the wealth and achieving the equality from the point of view of the management and supervision staff in the zakat institutions-Palestine is 4.15, 83.1 %. The term, reducing the unemployment is the first sector that gets the highest percentage, 85.2%. Then, the second term is ‘facing the poverty’ which gets 84.0 %. The term, achieving the equality is the third one and it gets 82.4%, finally, the term, distributing the wealth is fourth one and it gets 80.8%. The study also reveals that there are no statistically significant differences at the level of significance (0.05) between the average estimates of the sample members of the study in terms of discussing the role of the zakat in achieving the social security from the point of view of the management and supervision staff of the Palestinian zakat institutions. The main reason beyond this belongs to the variables; age, qualification, work duration and service. Hence, the study comes out with some recommendations, most notably that the strategic vision in the work of the zakat institutions in Palestine should include plans, programs and components necessary for the process of achieving community security, and give more attention to the programs of the zakat institutions in the use of large-scale funds to achieve continuous improvement in their work to contribute to a fair achievement. For wealth, taking equity and equity into account in accordance with the needs of beneficiaries.